P‐13.1: Novel OLED Low Frame Frequency Driving method with minimized Flicker. (24th February 2021) - Li, Jieliang; Yuan, Yong; Ding, Yuan; Huang, Wanming; Ke, Zhoulin; Zhang, Yuheng; He, Shui; Lai, Qingjun; Xu, Yuping
Abstract : We analyzed flicker of OLED and minimized it under low frame frequency with changing the emit pulse width and frequency. We also report a novel low frame frequency driving method for minimzing image flicker under −50dB although the average brightness is 450nit with attenuation −30nit during emission.